Inﬂuence of Murottal Al-Qur’an Ar-Rahman Letter to Decrease of Blood Pressure of Pregnant Women with Preeclampsia - Mulastin, Mulastin; ., Sugiharto (KnE Social Sciences, 2019)
Preeclampsia is one of the causes of the Maternal Mortality Rate (MMR). In Central Java Province in 2016 reached 109.65 from 100,000 live births. Data obtained from pregnant women with preeclampsia at the Kaliwungu holy health center were 64 pregnant women. One of the symptoms of preeclampsia is high blood, there are several ways to improve body condition with music therapy, and listen to murottal. The goal is to know the inﬂuence of murottal Al-Qur’an letter Ar-Rahman to blood presure of pregnant women who have preeclampsia. This type of research is an experimental study using the Quasy design experiment pretest-posttest control group design.Thepopulationofthisstudywereallpregnantwomenwhohadpreeclampsiaat Puskesmas Kaliwungu Kudus which were 64 pregnant women in September-October 2017, and the sample was pregnant women who had preeclampsia, 32 as intervention group and 32 as control group. Sampling techniques with quota sampling (non probability). Data analysis of the research with using the Independent T Test. The results of the research showed that the blood pressure were signiﬁcantly higher in intervension than the case of control groups. average systolic blood pressure in the intervention group was 122.78 mmHg and the control group was 126.75 mmHg with the results of the statistical test 0.001<P value so that there was an effect. There was a decrease in systolic blood pressure of 3.97 mmHg. While the average value of diastole blood pressure in the intervention group was 82.22 mmHg and the control group was 81.92 and the results of the statistical test were 0.015<P value. There is a decrease in diastolic blood pressure of 0.3 mmHg. Which means there is an Ar-Rahman letter’s morattal inﬂuence on blood pressure decrease in pregnant women who have preeclampsia. Expected at the time of ANC or at the time of pregnant mother class to be given listening murottal technique of Ar-Rahman letter by improvingservicesforpregnantmotherforpregnantmotherwhospendspreeclampsia. Keywords: Murottal Al-Qur’an, Ar-Rahman, Blood Pressure, Preeclampsia.